1981
DOI: 10.1159/000123173
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Partial Deafferentation of the Hypothalamus on Stress-Induced LH Suppression and Prolactin Release

Abstract: Stress of immobilization suppressed pulsatile LH release and decreased mean serum LH levels within 10 min, lasting at least for 2 h in ovariectomized rats. Anterior cuts (radius, 2 mm) at the level of the caudal border of the suprachi-asmatic nucleus, resulted in elimination of the stress-induced LH suppression. A smaller cut (radius, 1 mm) at the same level induced increased LH secretion without a period of inhibition in some rats by the stress. Extended anterior cut at the level of the border between the med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

1984
1984
1996
1996

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…Lesions of the retrochiasmatic area prevented the inhibition of pulsatile LH release in duced by electrical stimulation of the dorsal raphe nucleus [4]. Stimulation of the perisuprachiasmatic area lengthened the interval between LH pulses [8], Stress-induced suppres sion of pulsatile LH release was inhibited by the anterior neural deafferentation in ovariectomized rats [13]. Taken together with the present result, it is suggested that the mod ulatory, particularly inhibitory, influence comes from the rostral direction to the MBH.…”
Section: Discussionsupporting
confidence: 73%
“…Lesions of the retrochiasmatic area prevented the inhibition of pulsatile LH release in duced by electrical stimulation of the dorsal raphe nucleus [4]. Stimulation of the perisuprachiasmatic area lengthened the interval between LH pulses [8], Stress-induced suppres sion of pulsatile LH release was inhibited by the anterior neural deafferentation in ovariectomized rats [13]. Taken together with the present result, it is suggested that the mod ulatory, particularly inhibitory, influence comes from the rostral direction to the MBH.…”
Section: Discussionsupporting
confidence: 73%
“…It is uncertain, however, whether the acute elevation of circulating pro lactin levels in acutely stressed animals [ 13,20,21 ] may as well play a role in the refractoriness of the hypothalamic LH-RH neuron system to NMDA.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been reported that acute immobilization stress inhibits the existing pulsatile LH release in ovariectomized rats [12][13][14], In intact female rats, acute restraint or foot shock stress can eliminate the expected ovulation [15,16]. Pre vious studies have shown that corticotropin-releasing fac tor (CRF) and endogenous opioid peptides (EOP) are involved in the induction of the hypogonadotropic state by acute stress in the rat, since administration of a CRF antagonist [17] or EOP antagonists or antiserum [14-16, 18, 19], prior to the stress exposure, could inhibit the decline in LH secretion which was otherwise observed in acutely stressed rats.…”
Section: Introductionmentioning
confidence: 99%
“…However, an earlier time of onset of the pro-oestrous surge of LH occurred in rats bearing PM cuts interrupting caudal afférents to the hypothalamus. Previous works have indicated that interruption of caudal afférents to the mediobasal hypothalamus did not interfere with ovulation and normal cyclicity in the rat (Halász & Gorski 1967) and the guinea pig (Terasawa & Wiegand 1978) nor with the release of LH in ovariectomized rats (Kawakami & Higuchi 1981). The advanced release of LH by these cuts can not be assigned to the duration of the oestrous cycle and may rather be due to transection of fibres that inhibit LH secretion perhaps by way of sup¬ pressing the secretion from gonadotrophin releas¬ ing hormone-containing neurons.…”
Section: Discussionmentioning
confidence: 87%